Urinary long non-coding RNA GAS5 as a noninvasive diagnostic biomarker for renal fibrosis - Ying Yu; Yang-yang Niu; Ying-ying Zhang; Chen Yu (Renal Failure, 2025)
Background Renal fibrosis, the terminal pathological pathway of chronic kidney disease (CKD), lacks reliable noninvasive biomarkers for clinical assessment. Current diagnostic reliance on renal biopsy—despite its gold-standard status—poses risks of bleeding and sampling errors, necessitating alternatives. Long non-coding RNA growth arrest-specific 5 (GAS5) regulates fibrogenic pathways, but its utility as a liquid biopsy marker remains unexplored.Method This prospective cross-sectional study quantified GAS5 levels in paired plasma and urine samples from 198 CKD patients (stratified by renal fibrosis scoring: mild: <25%, moderate: 25–50%, severe: ≥50% fibrotic area) and 20 healthy controls. Multivariate regression models adjusted for cardiorenal confounders (hypertension, blood pressure, and so on) evaluated GAS5’s association with fibrosis.Results Plasma GAS5 levels increased with renal fibrosis severity, whereas urinary GAS5 exhibited progressive suppression. After adjusting for factors such as hypertension history, systolic and diastolic blood pressure, blood urea nitrogen, creatinine, eGFR, and uric acid, use of ACEI/ARB, multivariate analysis showed significant associations between urinary GAS5 level and renal fibrosis. ROC analysis revealed urinary GAS5’s superior diagnostic accuracy compared with eGFR and TGF-β1. AUCs of urinary GAS5 were even higher in moderate and severe renal fibrosis group.Conclusions While plasma GAS5 upregulation and urinary GAS5 suppression reflect inverse expression patterns in renal fibrosis, urinary GAS5 emerges as the dominant noninvasive biomarker due to its superior diagnostic performance (AUC = 0.868) and clinical accessibility.